Anthropometric knowledge and measurement evaluation among female volunteer community health workers in Depok - Sufyan, Dian Luthfiana; Arini, Firlia Ayu; Ilmi, Ibnu Malkan Bakhrul; Marjan, Avliya Quratul; Fatmawati, Iin (Alma Ata University Press, 2024)
Background: At the community level, assessment for children nutritional status is measured by female volunteer community health workers (FVCHW) through integrated health post (Posyandu). Based on initial observation, volunteers have sufficient knowledge of anthropometric measurement however, to put it into practice, common pitfalls remain found.Refreshment on basic knowledge and practical training on anthropometric assessment is needed.Objectives: As part of Kampung Caraka Project that attempts to empower locals to be deliberately aware of community health and well-being, this particular study aims to evaluate knowledge of FVCHW as well as their accuracy and precision on anthropometric assessment.Methods: This study is a quasi-experimental study with pre-posttest with control group design. The sample was purposively selected and 54 overweight adolescents were divided into a control group and two intervention groups. Education using healthy snacks quartet was conducted for 21 days from September to October 2023 in Makassar City. Data analysis was performed using Wilcoxon singed ranks test.Results: Results showed women with good precision for MUAC, height, head circumferences and length measurement were 23.1%, 23.1%, 53.8% and 33.3%, respectively. In contrast, only 7.7% of women had good accuracy on MUAC measurement. There is a significant difference of knowledge score before and after the education given (p-value 0.02, CI 95%).Conclusions: The cadre had good precision yet poor accuracy, implying the necessity of standardized procedure and regular equipment calibration prior to anthropometric measurement. There is a difference in mean scores before and after the education given, yet still denoted as low capacity. Further comprehensive education is highly required.